2009
DOI: 10.1111/j.1474-9726.2009.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of TGF‐β1 and Wnt in the systemic regulation and aging of satellite cell responses

Abstract: Muscle stem (satellite) cells are relatively resistant to cell-autonomous aging. Instead, their endogenous signaling profile and regenerative capacity is strongly influenced by the aged P-Smad3, differentiated niche, and by the aged circulation. With respect to muscle fibers, we previously established that a shift from active Notch to excessive transforming growth factor-beta (TGF-β) induces CDK inhibitors in satellite cells, thereby interfering with productive myogenic responses. In contrast, the systemic inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(184 citation statements)
references
References 61 publications
6
176
0
2
Order By: Relevance
“…Under normal conditions, without any stimuli, TGF-b1/ p-Smad signaling may be downregulated either by serum latent TGF-b1 or by lower levels of TGF-b1 receptors, whereas upon injury such as oxidative stress, aging, inflammation and so on, the active TGF-b1 and/or the expression of TGF-b1 receptor may be increased, thereby causing pSmad signaling to accelerate in HSCs. 41 MAP kinase activation in livers was associated with the extent of the liver injury and fibrosis. JNK has a role in CCl 4 -induced liver damage by stimulating the production of pro-inflammatory cytokines through AP-1 42 and/or NF-kB 43 and with its prolonged activation promotes cell death (necrosis and/or apoptosis) depending on cell type and stimulus and may have both pro-or anti-apoptotic effects in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, without any stimuli, TGF-b1/ p-Smad signaling may be downregulated either by serum latent TGF-b1 or by lower levels of TGF-b1 receptors, whereas upon injury such as oxidative stress, aging, inflammation and so on, the active TGF-b1 and/or the expression of TGF-b1 receptor may be increased, thereby causing pSmad signaling to accelerate in HSCs. 41 MAP kinase activation in livers was associated with the extent of the liver injury and fibrosis. JNK has a role in CCl 4 -induced liver damage by stimulating the production of pro-inflammatory cytokines through AP-1 42 and/or NF-kB 43 and with its prolonged activation promotes cell death (necrosis and/or apoptosis) depending on cell type and stimulus and may have both pro-or anti-apoptotic effects in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the secretion of the regulatory cytokine TGF-b1 during differentiation and the ability of young and old cells to respond to, and recover from, TGF-b1 treatment during differentiation. TGF-b1 is a key myogenic regulatory cytokine and studies suggest that its expression may be altered with age (Zentella & Massague, 1992;Carlson et al, 2009a). No significant difference in any of the parameters was observed between young and old donors.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-b1 production in early passage and senescent cells TGF-b1 is an important cytokine involved in regulating skeletal muscle myogenesis (Zentella & Massague, 1992;Carlson et al, 2009a). The ability of TGF-b1 to inhibit myoblast differentiation and to depress proliferation has been documented (Massague et al, 1986;Allen & Boxhorn, 1987;Greene & Allen, 1991).…”
mentioning
confidence: 99%
“…Similar studies were conducted in various organs such as Muscle [148], Skin [149] and Neuronal cells [150]. Heterochronic and isochronic transplant studies [151] have shown the increased proliferation rates of old islet β cells which were transplanted to young mice and of young islet β cells which were transplanted to young mice.…”
Section: The Effect Of Systemic Microenvironment and Ageingmentioning
confidence: 69%